Tadeusz Miciński and Russia: the First World War Years - Bajko, Marcin (Slavia Orientalis, 2020)
The author of the article deals with the subject of the Russian period of Tadeusz Miciński’s work (1873‑1918). The rationale here being the discovery of many ‘new’, previously unpublished articles by the writer. In turn, the context was published by G. Bobilewicz years ago: Tadeusz Miciński i Rosja. Szkic do tematu (2008). The author presents the state of research, discusses the previously unknown texts by the author of Nietota, and finally gives new facts about Miciński’s stay in Russia (from 1915‑1918). The author discusses the literary activity of Miciński from the First World War onwards. This encompasses largely journalistic texts: articles, manifestos, open letters, travel reports from the front and from the life of Polish soldiers fighting on the Eastern Front.
Keywords: journalism; Russia; Poland; Tadeusz Miciński (1873–1918); First World War; 1917